Peran Pancasila Terhadap Dinamika Sosial dan Komunikasi Masyarakat Indonesia dalam Pembangunan Yang Adil dan Berkelanjutan - Najma Ajmala Nisya Yurico; Siti Nirraysa; Angelina Sipayung; Audrey Cynthia Rose (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research explores the role of Pancasila in the social dynamics and communication of Indonesian society in the context of fair and sustainable development. Using a literature review approach, this study analyzes how the values of Pancasila influence communication patterns, social interactions, and national development. The findings indicate that Pancasila has a significant impact on shaping national identity, promoting dialogue and understanding, and strengthening principles of justice and participation in development. However, challenges such as divergent interpretations of Pancasila values, political polarization, and social inequality still affect the implementation of these values. Therefore, joint efforts from the government, civil society organizations, the private sector, and civil society are needed to enhance understanding, participation, and law enforcement regarding Pancasila values in order to create an inclusive, fair, and sustainable environment for all citizens.